2015
DOI: 10.1007/s12020-015-0616-8
|View full text |Cite
|
Sign up to set email alerts
|

Associations between a common variant near the MC4R gene and serum triglyceride levels in an obese pediatric cohort

Abstract: Polymorphisms near the MC4R gene may be related to an increased risk for obesity, but studies of variations in this gene and its relation to cardiometabolic profiles and food intake are scarce and controversial. The aim of this study is to evaluate the influence of the variants rs12970134 and rs17782313 near the MC4R gene in food intake, binge eating (BE) behavior, anthropometric parameters, body composition, metabolic profile, and cardiometabolic risk factors in obese children and adolescents. This is a cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
2
6
0
3
Order By: Relevance
“…Heterozygous subjects for the Ile251Leu SNP showed higher levels of total cholesterol and LDL-cholesterol. There are studies on the association between MC4R variants and other lipid markers in several populations [31,46].…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous subjects for the Ile251Leu SNP showed higher levels of total cholesterol and LDL-cholesterol. There are studies on the association between MC4R variants and other lipid markers in several populations [31,46].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, different genetic models have been used in previous studies, including the dominant model [57], the recessive model [58], and the additive model [59], and there are no conclusions yet which genetic model is the best. However, when investigating at the characterization of the MC4R knock-out mice, Cone, et al found that animals heterozygous for the melanocortin-4 receptor were intermediate to wild type and MC4R null mice in obesity-related phenotypes including growth rate, serum leptin concentrations, linear growth, and fasting serum insulin concentrations [45].…”
Section: Discussionmentioning
confidence: 99%
“…[50] To date, very few studies have been conducted to investigate the association between DNA methylation of MC4R and metabolic components in cord blood, although most genetic studies have shown that common variants near MC4R were associated with elevated TG levels and an increased risk of hypertriglyceridemia in obese children and adolescents. [51] In addition, genetic variants of MC4R have been found to lead to substantially higher postprandial response of TG levels in healthy subjects. [52] The active forms of MC4R decrease the activity of stearoyl-coenzyme A desaturase 1, which is involved in TG synthesis and affects LDL levels via the liver, resulting in decreased TG synthesis.…”
Section: Discussionmentioning
confidence: 99%